2019
DOI: 10.3390/cancers11121826
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeting Therapy against EGFR Family in Breast Cancer: Progress and Future Potentials

Abstract: The epidermal growth factor receptor (EGFR) family contains four transmembrane tyrosine kinases (EGFR1/ErbB1, Her2/ErbB2, Her3/ErbB3 and Her4/ErbB4) and 13 secreted polypeptide ligands. EGFRs are overexpressed in many solid tumors, including breast, pancreas, head-and-neck, prostate, ovarian, renal, colon, and non-small-cell lung cancer. Such overexpression produces strong stimulation of downstream signaling pathways, which induce cell growth, cell differentiation, cell cycle progression, angiogenesis, cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 124 publications
1
120
0
Order By: Relevance
“…In the present study, four genes were revealed to be mutated at a high frequency, including KIT, ERBB4, MET and IGF1R, which were mutated in 33.3% patients. These genes encode typical tyrosine-protein kinases or receptor tyrosine kinases that are cell surface receptors for multiple signaling pathways and serve an essential role in the regulation of cell survival, proliferation and apoptosis (42)(43)(44)(45). Mutations in these genes are important therapeutic targets of molecular targeted therapeutic drugs, such as the TKIs imatinib and sunitinib (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, four genes were revealed to be mutated at a high frequency, including KIT, ERBB4, MET and IGF1R, which were mutated in 33.3% patients. These genes encode typical tyrosine-protein kinases or receptor tyrosine kinases that are cell surface receptors for multiple signaling pathways and serve an essential role in the regulation of cell survival, proliferation and apoptosis (42)(43)(44)(45). Mutations in these genes are important therapeutic targets of molecular targeted therapeutic drugs, such as the TKIs imatinib and sunitinib (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR, also called ErbB1 or HER1, is a member of the ErbB family of receptors, which are transmembrane glycoproteins that stimulate their corresponding signaling pathway, including the KRAS-MEK1/2-ERK1/2 pathway, phosphoinositide 3-kinase (PI3K)-AKT kinase pathway, and STAT signaling pathway [36,37]. Evidence is accumulating for a critical role played by the EGFR-mediated signaling pathway in cell proliferation, survival, angiogenesis, and cancer metastasis [38].…”
Section: Discussionmentioning
confidence: 99%
“…ERBB2, commonly referred to as HER2, encodes a member of the epidermal growth factor receptor family of receptor tyrosine kinases, it is amplified and/or overexpressed in 20-30% of invasive breast carcinomas [13]. Amplification and/or overexpression of this gene have also been reported in many other cancers including ovarian and gastric cancer [14][15][16]. ERBB2 binds tightly to other ligand-bound EGF receptor family members to form a heterodimer, stabilizing ligand binding and enhancing kinase-mediated activation of downstream signaling pathways, such as PI3K/AKT activation and RET signaling [17].…”
Section: Discussionmentioning
confidence: 99%